Numerical Calculation of Thermal Stress in Cement Rotary-kiln Foundation at an early age - Adek Tasri (Department of Mechanical Engineering, Universitas Andalas, 2021)
This article discusses the early-age thermal stress, caused by the hydration heat, of a rotary kiln concrete foundation. We measure the hydration heat using an adiabatic calorie meter and perform finite volume numerical calculations to obtain the temperature distribution and finite element calculation to determine the thermal stress. The numerical simulation showed significant temperature differences between the core region and surface of the concrete. Compressive stress developed at the core, and tensile stress developed at the surface of the concrete during a heating period. The compressive stress was lower than the concrete compressive strength. The tensile stress was higher than the concrete tensile strength. So that crack developed in the surface. Heat treatment such as post-cooling or pre-cooling was needed to avoid the crack.